1976
DOI: 10.1002/chin.197618314
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: COORDINATION COMPLEXE

Abstract: Die offenkettigen Tetrathioäther (IV) wurden durch Reaktion von Na‐methylsulfid mit dem entsprechenden Chloralkohol (I) in absolutem Äthanol, Chlorierung des entstehenden Hydroxyalkylmethylsulfids (IIa) mit Thionylchlorid in wasserfreiem Chloroform und Umsetzung des Derivats (IIb) mit den Dithiolaten (III) in Äthanol dargestellt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…Reaction of NiX 2 (X = Cl, Br or I) with [16]aneSe 4 (1,5,9,13-tetraselenacyclohexadecane) under anhydrous conditions in n-butanol yielded trans-[NiX 2 ([16] [16]aneSe 4 complexes were obtained via nickel K-edge EXAFS (extended X-ray absorption fine structure), and the results compared with related complexes. A ligand field analysis of the UV/VIS spectra of [NiX 2 ([16]aneSe 4 )] and of the tetrathioether analogues [NiX 2 ([16]aneS 4 )] ( [16]aneS 4 = 1,5,9,13-tetrathiacyclohexadecane) showed that the ligand fields produced by 16-membered ring macrocycles [Dq(xy)] lie in the order N 4 > S 4 > Se 4 , with MeSeCH 2 CH 2 SeMe affording a stronger field that [16]aneSe 4 due to the smaller chelate ring size.…”
Section: Macrocyclic Selenoether Complexes Of Nickel(ii) Synthesis An...mentioning
confidence: 99%
See 4 more Smart Citations
“…Reaction of NiX 2 (X = Cl, Br or I) with [16]aneSe 4 (1,5,9,13-tetraselenacyclohexadecane) under anhydrous conditions in n-butanol yielded trans-[NiX 2 ([16] [16]aneSe 4 complexes were obtained via nickel K-edge EXAFS (extended X-ray absorption fine structure), and the results compared with related complexes. A ligand field analysis of the UV/VIS spectra of [NiX 2 ([16]aneSe 4 )] and of the tetrathioether analogues [NiX 2 ([16]aneS 4 )] ( [16]aneS 4 = 1,5,9,13-tetrathiacyclohexadecane) showed that the ligand fields produced by 16-membered ring macrocycles [Dq(xy)] lie in the order N 4 > S 4 > Se 4 , with MeSeCH 2 CH 2 SeMe affording a stronger field that [16]aneSe 4 due to the smaller chelate ring size.…”
Section: Macrocyclic Selenoether Complexes Of Nickel(ii) Synthesis An...mentioning
confidence: 99%
“…1,2 In contrast, macrocyclic thioethers are able to form stable complexes with most transition metals. 3 The synthesis 4 of macrocyclic selenoethers including [16]aneSe 4 opens up the possibility of similarly enhanced M᎐Se binding, and we have reported complexes with a variety of platinum metal centres, viz. [M( [16]aneSe 4 )] 2ϩ (M = Pd or Pt), 5 [PtX 2 ([16]aneSe 4 )] 2ϩ (X = Cl or Br), 6 [MX 2 ([16] ([16]aneSe 4 )] ϩ 10 both of which benefit from the kinetically inert metal centres.…”
Section: Macrocyclic Selenoether Complexes Of Nickel(ii) Synthesis An...mentioning
confidence: 99%
See 3 more Smart Citations